Application of the PQ4R Method to Improve Reading Comprehension Ability of Grade IV Students at Wanajaya 02 Elementary School - Anisa Safitri; Rini Endah Sugiharti; Yudi Budianti (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Researchers implemented the PQ4R method to improve reading comprehension skills in fourth-grade students. This study used the Classroom Action Research (CAR) method, which was conducted in two cycles. In its implementation, researchers inserted innovations in the form of the use of image media as a supporting tool for learning activities. This was done because researchers found that students tended to be less enthusiastic in reading texts that only consisted of writing without images. In addition, students quickly became bored with individual learning methods without any interesting variations. The application of the PQ4R method (Preview, Question, Read, Reflect, Recite, Review) with the support of image media aimed to motivate students to be more active in learning and understanding the material presented. The results of the study showed a significant increase in students' reading comprehension skills. In cycle 1, only about 60% of students showed good understanding, while in cycle 2, this figure increased to 94%. This increase indicates that the use of image media in learning can help students understand the material better and increase their interest in reading. Therefore, the application of the PQ4R method accompanied by image media has proven effective in improving the reading comprehension skills of fourth-grade students. Thus, this research can be concluded as successful, and can be used as a reference for similar learning methods in other classes.